THE USE OF SPEECH ACTS AMONG FRONT OFFICE STUDENTS IN LEARNING EFL AT SMK PARISATA TRIATMAJAYA SINGARAJA - ., I Putu Sujana; ., Prof. Dr. Dewa Komang Tantra,Dip.,App.; ., Dewa Ayu Eka Agustini, S.Pd., M.S. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Tujuan penelitian ini adalah untuk menganalisis tindak tutur yang dipakai oleh siswa front office untuk menjalankan tugas-tugas seorang resepsionis di SMK Pariwisata Triatmajaya Singaraja, menganalisis gaya bahasa yang dipakai dalam menjalankan tugas-tugas resepsionis, dan menganalisis errors yang diucapkan oleh siswa di SMK Pariwisata Triatmajaya Singaraja. Penelitian ini adalah penelitian kualitatif dalam bidang penelitian lapangan. Subjek dari penelitian ini adalah kelas XII AP1 jurusan akomodasi perhotelan. Data diperoleh melalui metode eliciting data, rekaman, dan transkripsi. Data yang diperoleh dianalisis berdasarkan Searle’s Taxonomy, yaitu: Representatives, Directives, Commissives, Expressives and Declaratives. Hasil penelitian ini menunjukkan bahwa tindak tutur locutionary yang digunakan oleh siswa front office adalah directives asking, directives requesting, directives commanding, directives inviting, directives permiting, directives welcoming, representatives insist, representatives state, representatives report, representatives suggest, commissives promise, commissives appointment, commissives offer, expressive thanking, expressive apologizing, dan declaratives promoting. Gaya bahasa yang dipakai oleh siswa front office dalam menjalankan tugas- tugas front office dalam kategori bahasa resmi adalah 83.75% menggunakan bahasa formal dan 16.25% menggunakan bahasa tidak formal. Selain itu, errors yang dilakukan dalam tindak tutur dan gaya bahasa siswa front office tersebut adalah dalam tata bahasa yaitu 5.69% dan diksi yaitu 12.08%. Sebagian besar siswa front office tersebut melakukan errors karena gangguan dari stuktur bahasa asli terhadap stuktur bahasa asing. Kata Kunci : SMK, belajar EFL, tindak tutur, gaya bahasa, errors This research aimed at analyzing the locutionary acts used in utilizing front office tasks by the students of front office at Vocational School or Sekolah Menengah Kejuruan (SMK) Pariwisata Triatmajaya Singaraja, analyzing speech styles used in utilizing the front office tasks by the students of front office in terms of formality at SMK Pariwisata Triatmajaya Singaraja and analyzing errors are committed in their speeches in terms of grammar and diction at SMK Pariwisata Triatnajaya Singaraja. This study was qualitative research in terms of field research. The subjects of this study were the front office students of SMK Pariwisata Triatnajaya singaraja especially the XII AP1 Class. The data were obtained through eliciting data, recording and data transcription. The obtained data were analyzed based on Searle’s Taxonomy, namely: Representatives, Directives, Commissives, Expressives and Declaratives. The result of this study shows that the locutionary acts in utilizing front office tasks by the students of front office at SMK Pariwisata Triatmajaya Singaraja were directives asking, directives requesting, directives commanding, directives inviting, directives permiting, directives welcoming, representatives insist, representatives state, representatives report, representatives suggest, commissives promise, commissives appointment, commissives offer, expressive thanking, expressive apologizing, and declaratives promoting. The speech styles used in utilizing front office tasks by the students of front office in terms of formality among prospective front officers at SMK Pariwisata Triatmajaya Singaraja were 83.75% of formal language and 16.25% of informal language. Besides, the errors that were committed in their speeches in terms of grammar and diction were 5.69% errors of grammar and 12.08% errors of diction. Most of the prospective front officers’ errors that they committed were call as interlanguage errors. These errors happened when the interference of students’ first language occurred in the target language. keyword : vocational school, learning EFL, speech acts, speech styles, errors.